PEMANFAATAN TEKNOLOGI DIGITAL UNTUK MENINGKATKAN MINAT BACA SISWA SEKOLAH DASAR - Aziz, Abdul; Inda Fajrani, Alya; Shalliwa Khairaty; Adrias; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has influenced the field of education, including students’ reading literacy in elementary schools. Today, children tend to use digital devices more for entertainment rather than educational activities. Data from UNESCO shows that Indonesia’s literacy index is very low, with only 0.001% of the population categorized as avid readers, while the average Indonesian child spends around 9 hours per day looking at gadget screens. This condition indicates that the potential of digital technology as a tool to support literacy has not been utilized optimally. This article aims to examine the use of digital technology as a means to improve literacy among elementary school students and to identify effective forms of digital media in learning, using a literature study method. The results of the study show that the directed use of digital technology has been proven to significantly increase students’ interest in and ability in literacy. One study recorded an increase in reading interest from 35% to 75% after implementing creative technology-based methods for three months. The use of instructional video media among 149 students in Jakarta also showed a significant effect, with 43.6% of students reaching a high level of reading interest. Digital literacy programs combined with reading habits before lessons are effective in building literacy habits while also helping parents guide the wise use of gadgets. Effective strategies work through four main mechanisms: habituation, modeling, interaction, and motivation reinforcement. The success of literacy programs is also determined by teacher competence, support from the school ecosystem, and active involvement of parents. Digital technology will be effective when it is integrated pedagogically and purposefully into the literacy learning process.